Small Alarmone Synthetases RelP and RelQ of Staphylococcus aureus Are Involved in Biofilm Formation and Maintenance Under Cell Wall Stress Conditions - Salzer, Andrea; Keinhörster, Daniela; Kästle, Christina; Kästle, Benjamin; Wolz, Christiane (Frontiers in Microbiology, 2020)
The stringent response is characterized by the synthesis of the alarmone (p)ppGpp. The phenotypic consequences resulting from (p)ppGpp accumulation vary among species, and for several pathogenic bacteria, it has been shown that the activation of the stringent response strongly affects biofilm formation and maintenance. In Staphylococcus aureus, (p)ppGpp can be synthesized by the RelA/SpoT homologue Rel upon amino acid deprivation or by the two small alarmone synthetases RelP and RelQ under cell wall stress. We found that relP and relQ increase biofilm formation under cell wall stress conditions induced by a subinhibitory vancomycin concentration. However, the effect of (p)ppGpp on biofilm formation is independent of the regulators CodY and Agr. Biofilms formed by the strain HG001 or its (p)ppGpp-defective mutants are mainly composed of extracellular DNA and proteins. Furthermore, the induction of the RelPQ-mediated stringent response contributes to biofilm-related antibiotic tolerance. The proposed (p)ppGpp-inhibiting peptide DJK-5 shows bactericidal and biofilm-inhibitory activity. However, a non-(p)ppGpp -producing strain is even more vulnerable to DJK-5. This strongly argues against the assumption that DJK-5 acts via (p)ppGpp inhibition. In summary, RelP and RelQ play a major role in biofilm formation and maintenance under cell wall stress conditions.